Impact retrenchment of workers - Maulad Bahrol, Khadijah; Humaid Alhosani, Adnan Ali Hassan; Abdullah, Mohd Fahmy; Ismail, Fadillah (Penerbit Uthm, 2019)
Retrenchment in layman’s term is known as ‘reduction of workforce’ whereas in lawful terms it is respected as “termination of contract’. The industrial court restricted the utilization of the term ‘retrenchment’ to cruel a release of excess work. In the HR term, ‘retrenchment’ is characterized as a movement to legitimately end any work contract with the representative by advertising a recompense bundle. Such offer to conserve may come into as common acknowledgment or constrained upon by one party which of course would be the employer (Retrenchment – Understanding, Process and Procedures - rss - NHRC, 2014).